Exercise-Induced Ventricular Ectopy and Cardiovascular Mortality in Asymptomatic Individuals - Refaat, Marwan M; Gharios, Charbel; Moorthy, M Vinayaga; Abdulhai, Farah; Blumenthal, Roger S; Jaffa, Miran A; Mora, Samia (Journal of the American College of Cardiology, 2021)
The prognosis of exercise-induced premature ventricular contractions (PVCs) in asymptomatic individuals is unclear. This study sought to investigate whether high-grade PVCs during stress testing predict mortality in asymptomatic individuals. A cohort of 5,486 asymptomatic individuals who took part in the Lipid Research Clinics prospective cohort had baseline interview, physical examination, blood tests, and underwent Bruce protocol treadmill testing. Adjusted Cox survival models evaluated the association of exercise-induced high-grade PVCs (defined as either frequent (>10 per minute), multifocal, R-on-T type, or ≥2 PVCs in a row) with all-cause and cardiovascular mortality. Mean baseline age was 45.4 ± 10.8 years; 42% were women. During a mean follow-up of 20.2 ± 3.9 years, 840 deaths occurred, including 311 cardiovascular deaths. High-grade PVCs occurred during exercise in 1.8% of individuals, during recovery in 2.4%, and during both in 0.8%. After adjusting for age, sex, diabetes, hypertension, lipids, smoking, body mass index, and family history of premature coronary disease, high-grade PVCs during recovery were associated with cardiovascular mortality (hazard ratio [HR]: 1.82; 95% CI: 1.19-2.79; P = 0.006), which remained significant after further adjusting for exercise duration, heart rate recovery, achieving target heart rate, and ST-segment depression (HR: 1.68; 95% CI: 1.09-2.60; P = 0.020). Results were similar by clinical subgroups. High-grade PVCs occurring during the exercise phase were not associated with increased risk. Recovery PVCs did not improve 20-year cardiovascular mortality risk discrimination beyond clinical variables. High-grade PVCs occurring during recovery were associated with long-term risk of cardiovascular mortality in asymptomatic individuals, whereas PVCs occurring only during exercise were not associated with increased risk.